2019
DOI: 10.1002/2211-5463.12635
|View full text |Cite
|
Sign up to set email alerts
|

Panax notoginseng saponins alleviate skeletal muscle insulin resistance by regulating the IRS1–PI3K–AKT signaling pathway and GLUT4 expression

Abstract: Panax notoginseng saponins ( PNS ) are a commonly used traditional medicine to treat diabetes in China. Recent studies have confirmed their anti‐diabetic effects, but the underlying mechanisms have remained unclear. The present study was designed to explore whether PNS decrease hyperglycemia by improving insulin sensitivity in skeletal muscle and to elucidate the molecular mechanisms. The anti‐diabetic effects of PNS were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…Skeletal muscle is responsible for a significant fraction of glucose uptake from the blood stream in the insulin-stimulated state 29 . More than 60% of blood glucose is absorbed by skeletal muscle 30,31 . And in growing broiler chickens, with the rapid increase of skeletal muscle mass, it is likely that glucose uptake by the skeletal muscles increases in importance 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle is responsible for a significant fraction of glucose uptake from the blood stream in the insulin-stimulated state 29 . More than 60% of blood glucose is absorbed by skeletal muscle 30,31 . And in growing broiler chickens, with the rapid increase of skeletal muscle mass, it is likely that glucose uptake by the skeletal muscles increases in importance 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Protein extraction procedures were previously described (Boizard et al, ; Bui et al, ; DeFronzo, ; Guo et al, ; Han et al, ; Violletet al, ). In short, tissue samples were homogenized and later quantified using the Pierce BCA Protein Assay Kit (Thermo Fisher Scientific, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The skeletal muscle is a significant organ for controlling the postprandial glucose consumption and storage under the signaling of insulin. Under metabolic disorders, reports demonstrated that inflammation and oxidative stress impair the insulin signaling to maintain the glucose homeostasis in skeletal muscles (Guo et al, ). In contrast, improving insulin sensitivity of skeletal muscle has been demonstrated to be an effective strategy in controlling blood glucose levels (DeFronzo, ; Smith & Muscat, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although altered expression of Ppargc1a mRNA in skeletal muscle might be one of causes improve the glucose intolerance in middle-aged mice, the results of the present study showed no changes between Control and High fat groups at 13-mo-old. Insulin receptor substrate IRS1 mediates insulin-derived signal via phosphorylation, which activates its downstream effector, AKT, to cause GLUT4 translocation to the membrane [12]. According to the result showing no change in Irs1 mRNA expression after high fat diet feeding, it was suggested that the level of gene expression was not related to glucose intolerance in skeletal muscle.…”
Section: Metabolic Impairmentmentioning
confidence: 99%
“…The THUN-DERBIRD qPCR Mix (TOYOBO) was used for PCR reaction following manufacturer-recommended dilution procedures. Genes that are reportedly related to glucose tolerance or type 2 diabetes in skeletal muscle of mice were targeted to analyze the regulation of gene expression [9][10][11][12][13][14][15]. Primer pairs for the gene expression analysis are shown in Table 1.…”
Section: Chromatin Immunoprecipitation (Chip)mentioning
confidence: 99%